Characterizing Salmonella enterica Serovar Choleraesuis, var. Kunzendorf: A Comparative Case Study - Longo, Alessandra; Petrin, Sara; Mastrorilli, Eleonora; Tiengo, Alessia; Lettini, Antonia Anna; Barco, Lisa; Ricci, Antonia; Losasso, Carmen; Cibin, Veronica (Frontiers in Veterinary Science, 2019)
Different Salmonella serovars generally display different antigenic formulae, but there are some exceptions. For instance, the same antigenic formula, 6,7:c:1,5, is shared by Salmonella enterica serovar Paratyphi C, Typhisuis and Choleraesuis. Moreover, three biotypes have been described within the S. Choleraesuis serovar. A distinction among such biotypes can only be based on biochemical behaviors (biotyping) posing serious concerns when rapid characterization is required. The study of an outbreak of severe epizootic salmonellosis in wild boars occurred in Italy between 2012 and 2014 and the typing of the isolates recovered from the outbreak were used to test different approaches for serovar identification. A number of 30 S.Choleraesuis var. Kunzendorf isolates from the outbreak were typed by means of four different methods to derive serovar and biotype: i) slide agglutination method followed by biochemical tests, ii) suspension array xMAP® Salmonella Serotyping Assay (SSA), iii) whole genome sequencing (WGS) and data analysis using SeqSero tool and iv) whole genome sequencing (WGS) and data analysis using Salmonella TypeFinder tool. Slide agglutination, xMAP® SSA and WGS followed by SeqSero analysis are methods that infer the serovars according to the White-Kauffmann-Le Minor (WKL) scheme, based exclusively on antigens. Using these methods, isolates with incomplete antigenic formulae could be misleadingly excluded from an outbreak. On the contrary, WGS followed by Salmonella TypeFinder data analysis, which predicts the serotype on the basis of Multilocus sequence typing (MLST), might be able to cluster together isolates belonging to the same outbreak irrespective of the antigenic formula. Results suggest the benefit of routine use of a combination of in silico MLST and antigenic formula analysis to solve specific ambiguous case studies for outbreak investigation purposes.